Integration of Local Wisdom Values into Environment Law Development in Bali (Lembaga Contrarius Indonesia, 2026)
This study explores the integration of Balinese local wisdom values into the development of environmental law as a means to achieve a sustainable, equitable, and culturally rooted environmental governance system. The research adopts a socio-legal approach, examining how centralistic and sectoral environmental regulations have often failed to preserve ecological balance due to neglect of local traditions and community participation. By analyzing key philosophical foundations such as Tri Hita Karana, Tat Twam Asi, Rwa Bhineda, and Karma Phala, the paper argues that local wisdom embodies moral, spiritual, and ecological principles that can strengthen the effectiveness of environmental law. These values not only serve as ethical guidelines but also as practical frameworks for harmonizing human–nature–God relationships in environmental management. The study concludes that integrating local wisdom into regional legal instruments is essential to enhance community involvement, empower traditional institutions, and ensure environmental justice. Such integration offers a model for developing an adaptive and culturally resonant environmental legal system, potentially replicable across Indonesia.